An investigation of the diners' brand love in the value co-creation process. (December 2020) - Junaid, Muhammad; Hussain, Khalid; Asghar, Muhammad Mansoor; Javed, Muzhar; Hou, Fujun; Liutiantian,
Abstract: Current research marks the first attempt to investigate the precursors and consequences of brand love in the process of service co-creation in the hospitality sector by taking diners' participation and perceived value as antecedents and three types of diners' well-being as the outcomes of brand love in a realistic co-creation setting (a Chinese hotpot cuisine restaurant). Using 500 responses, this study finds that information-seeking, responsible behavior and personal interaction increase perceived value, whereas information-seeking, personal interaction, and perceived value increase brand love. Perceived value mediates the relationships of information seeking, responsible behavior and personal interaction with brand love. Brand love directly effects all dimensions of diners' well-being, whereas, information-seeking, responsible behavior and personal interaction indirectly impact all dimensions of well-being. Furthermore, self-perceived mastering negatively moderates the participation—perceived value, and participation—brand love relationships.